Memory, Remembering, and Oblivion in Active Narrative Interviewing. (February 2014) - Gemignani, Marco
Research interviewing is not just a practice of exchanging data through communication and collection. Rather, the qualitative interview is an active process in which participants and researchers take part in a situated co-construction of meanings and memories. In this article, I argue for viewing memories and the acts of storing, accessing, and telling the past as relational processes in which the researcher's position shifts from collector to co-constructor. Moving away from seeing participants as "informational commodities" and data as merchandise, I problematize the assumption that participants' memories may simply be accessed through narratives, which serve as sources of "data." I suggest that a possible way to gain a complex view on memory and remembering is by focusing on both the told and the untold, the remembered and the forgotten. From this epistemological viewpoint, a narrative focus on the untold and forgotten contributes to the constructive potential of the inquiry process.